VALIDITAS MEDIA INTERAKTIF “SASANA BUDAYA” SEBAGAI SARANA PEMBELAJARAN KEBERAGAMAN BUDAYA DI KELAS IV SD - Putri Maharani; Silvi Mutia; Riska Ayuk Cahyani; Syeh Priyadi; Satria Firmansyah; Much Arsyad Fardani (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2025)
This research aims to test the validity of the interactive learning media "Sasana Budaya" on the subject of cultural diversity in the fourth-grade elementary school class. The research uses the ADDIE development model with a Research and Development (R&D) approach. In the process, the ADDIE model is simplified into four main stages: Analysis, Design, Development, and Implementation. The instruments used include validation sheets for subject matter and media experts, as well as questionnaires for teacher and student responses. The validation results showed a score of 94.67% for the media and 94.11% for the subject matter. The one-to-one trial conducted with five students resulted in a score of 96%, while the teacher's response reached 96.47%. Based on these results, the interactive media "Sasana Budaya" is declared very suitable for use as a means of teaching cultural diversity in elementary schools.